2021
DOI: 10.1002/cctc.202001949
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Acyl Group Transfer of o‐Alkynylphenol Esters Accompanied by C−O Bond Fission for Synthesis of Benzo[b]furan

Abstract: Herein, we report the nickel-catalyzed cascade CÀ O bond cleavage/cyclization of ortho-alkynylphenyl ester to construct a 3-acylbenzo[b]furan skeleton. As a result of reaction condition screening, the Ni(0)/IAd (1,3-Di(1-adamantyl)imidazole-2ylidene) system was found to be optimal for catalytic conversion. Interestingly, the reaction exclusively gives 3acylbenzo[b]furan instead of a decarbonylated product fre-quently observed in reactions mediated by acyl-nickel species. The catalyst loadings could be reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…However, both used Ni catalysts. 20,22) Here, we report unprecedented Pd-catalyzed migratory cycloisomerization of 3-o-alkynylphenoxy acrylic acid derivatives to give 2,3-disubstituted benzofurans (Fig. 1, C).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, both used Ni catalysts. 20,22) Here, we report unprecedented Pd-catalyzed migratory cycloisomerization of 3-o-alkynylphenoxy acrylic acid derivatives to give 2,3-disubstituted benzofurans (Fig. 1, C).…”
Section: Introductionmentioning
confidence: 83%
“…Migratory groups on aromatic nitrogen in indole synthesis are carbonyl, [3][4][5][6][7] alkoxyalkyl, [8][9][10][11] propargyl, 12) allyl, 13) and sulfonyl [13][14][15][16] groups. On the other hand, migratory groups on phenol in the benzofurans synthesis are alkoxyalkyl, 8) allyl, 16) boryl, 17) vinyl 18) propalgyl, 19) and carbonyl 20) groups. Transition metals used in the migratory cycloisomerization are Pd, Ni, Ru, Rh, Au, and Pt.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, we reported nickel(0)catalyzed migratory cycloisomerization of o-alkynylphenyl ester 3, giving 2,3-disubstituted benzofuran 4 (Scheme 1-(c)). [5] DFT calculation revealed that the reaction proceeded via oxanickelacyclopentene III formed by oxidative cycloaddition of alkyne and C=O bond of the ester moiety in 3 to a nickel(0) catalyst, which was successively isomerized to the intermediates IV, V, and VI, finally giving the product 4. Oxidative cycloaddition involving the C=O bond of an ester is uncommon compared with oxidative cycloaddition involving the C=O bond of aldehyde or ketone, and we therefore decided to investigate migratory cycloisomerization of oalkynylanilide 5 as the substrate instead of 3.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the kinetically favorable pathway and full catalytic cycle remain unclear. Although several theoretical studies on C–O bond activation mechanisms by Ni complexes (e.g., C­(phenyl)–O bond activation) have been reported, theoretical studies on Ni-catalyzed C­(vinyl)–O bond activation mechanisms are rather limited to the best of our knowledge. In the present study, we thus investigated the full catalytic cycle in the synthesis of Ni-catalyzed 2,3-disubstituted benzofurans using DFT calculations.…”
Section: Introductionmentioning
confidence: 99%